2009
DOI: 10.1007/s10811-009-9408-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ulva spp. as a temporary nutrient sink in a coastal lagoon with oyster cultivation and upwelling influence

Abstract: Bahía San Quintín is a coastal lagoon with large Ulva biomass and upwelling influence. Previous observations suggest that Ulva has increased recently as a result of oyster cultivation. To evaluate the possible role of Ulva as a temporary nutrient sink, biomass and tissue C, N, and P were determined seasonally. Maximum biomass was present during spring and early summer (1,413-1,160 t (dry)) covering about 400 ha. However, the biomass decreased to 35 t (dry) by winter. The mean annual percentage of Ulva C, N, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Nevertheless, it has been observed in field studies that microalgae are sometimes suppressed by macroalgae at high nutrient availability (Smith and Horne, 1988; Sfriso et al, 1989;Sfriso and Pavoni, 1994). Although a high rate of nutrient uptake has been reported particularly for Ulva species (see e.g., Zertuche-Gonzá lez et al, 2009;Luo et al, 2012), we excluded the hypothesis that the inhibitory effect observed in the co-culture experiments was due to nutrient competition, as nutrient levels in both D. dichotoma and U. rigida co-cultures showed values comparable to those of the control and even higher than those in co-cultures of R. pseudopalmata where no inhibition was observed. Changing in pH in surrounding medium due to macroalgae growth is a common event, as high rates of photosynthesis may drawdown CO 2 , increasing pH levels and making the environment unsuitable for microalgal growth (Goldman et al, 1982;Taraldsvik and Myklestad, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been observed in field studies that microalgae are sometimes suppressed by macroalgae at high nutrient availability (Smith and Horne, 1988; Sfriso et al, 1989;Sfriso and Pavoni, 1994). Although a high rate of nutrient uptake has been reported particularly for Ulva species (see e.g., Zertuche-Gonzá lez et al, 2009;Luo et al, 2012), we excluded the hypothesis that the inhibitory effect observed in the co-culture experiments was due to nutrient competition, as nutrient levels in both D. dichotoma and U. rigida co-cultures showed values comparable to those of the control and even higher than those in co-cultures of R. pseudopalmata where no inhibition was observed. Changing in pH in surrounding medium due to macroalgae growth is a common event, as high rates of photosynthesis may drawdown CO 2 , increasing pH levels and making the environment unsuitable for microalgal growth (Goldman et al, 1982;Taraldsvik and Myklestad, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…; Jousson et al, 2000;Walters et al, 2006), and Baja California (Ulva spp. ; Jorgensen et al, 2010;Zertuche-Gonzá lez et al, 2009) that have displaced native algal species and modified habitat, leading to losses in living resources and economic costs for eradication.…”
Section: Other Habsmentioning
confidence: 99%
“…Macroalgae are known to display an enormous capacity for the assimilation of nutrients (Valiela et al, 1997;Neori et al, 2004;Zertuche-Gonzá lez et al, 2009) and are purposefully used in many parts of the world to reduce nutrients levels in coastal waters (Neori et al, 2004;Carmona et al, 2006;Chopin et al, 2001Chopin et al, , 2008. Given that many HABs are directly or indirectly promoted by nutrients (Heisler et al, 2008;Anderson et al, 2008), macroalgae may reduce the occurrence of HABs by reducing the levels of nutrients available in the water column.…”
Section: Mechanisms For the Observed Effects And Potential Of Applicamentioning
confidence: 99%
“…Another group of autotrophs promoted by eutrophication in coastal ecosystems is macroalgae (Valiela et al, 1997;Valiela and Cole, 2002;Valiela, 2006). Many species of macroalgae are capable of rapid growth in the presence of high nutrient concentration and have a high assimilative capacity for nutrients thus act as nutrient sinks (Valiela et al, 1997;Neori et al, 2004;Zertuche-Gonzá lez et al, 2009). Like HABs, the overgrowth of macroalgae can be also considered harmful, as they can outcompete and replace seagrass beds, cover other critical benthic habitats, and promote diel hypoxia in estuaries (Valiela et al, 1997;Valiela and Cole, 2002;Valiela, 2006;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%